Answer:
4
x
−
1
3
y
=
−
2
To convert this equation to slope-intercept form, solve for
y
.
Subtract
4
x
from both sides.
−
1
3
y
=
−
2
−
4
x
Simplify
−
1
3
y
to
−
y
3
−
y
3
=
−
2
−
4
x
Multiply both sides times
3
.
−
y
=
−
2
(
3
)
−
4
x
(
3
)
Simplify.
−
y
=
−
6
−
12
x
Rearrange the right side.
−
y
=
−
12
x
−
6
Multiply both sides times
−
1
.
y
=
12
x
+
6
m
=
12
and
b
=
6
.
Step-by-step explanation:
Answer:
x+3x+4=3+3 → x=![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
x+3x+4=3+3
4x+4=6
4x=2
x=![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
Answer:
-4+7h
Step-by-step explanation:
Answer:
1
Step-by-step explanation:
9 - 4 x 2
4 x 2 = 8
9 - 8 = 1
Answer:
tt
Step-by-step explanation:
7vito6u